HHLA2 predicts improved prognosis of anti-PD-1/PD-L1 immunotherapy in patients with melanoma - Huang, Fu-xue; Wu, Jun-wan; Cheng, Xia-qin; Wang, Jiu-hong; Wen, Xi-zhi; Li, Jing-jing; Zhang, Qiong; Jiang, Hang; Ding, Qiu-yue; Zhu, Xiao-feng; Zhang, Xiao-shi; Ding, Ya; et al. (Frontiers in Immunology, 2022)
Background: As a recognized highly immunogenic tumor, immune checkpoint blockades (ICB) have been widely used as a systemic treatment option for melanoma. However, only about half of treated patients could benefit from it in Caucasians, and only about 15% in Chinese melanoma patients. Robust predictive biomarkers are needed. HHLA2, a new-found member of B7 family, is generally expressed in kinds of tumors, such as melanoma. This study focuses on illustrating the prognostic value of HHLA2 in melanoma immunotherapy and its association with tumor-infiltrating lymphocytes. Methods: HHLA2 expression in pan-cancer and the association with prognosis and immune microenvironment were identified by analyzing gene expression profiles from TCGA database with selected bioinformatics tools and methods. Tumor tissues from 81 cases with advanced and unresectable melanoma were collected for detecting HHLA2 and CD8 levels by immunohistochemistry. Results: HHLA2 was found to be ubiquitously expressed in pan-cancer with high level and correlate with the prognosis of patients. Further comprehensive analysis from TCGA database demonstrated that the highly expressed HHLA2 was remarkably correlated with better prognosis, high infiltration status of various immune-active cells and immune activated pathways in skin cutaneous melanoma (SKCM). Moreover, immunohistochemistry (IHC) analyses of FFPE tissue from melanoma patients revealed that HHLA2 high expression was strongly related to improved response to ICB and indicated a longer progression-free survival (PFS) and overall survival (OS). Besides, HHLA2 expression was found to have a positive association with the density of CD8+ TILs. Conclusion: Our findings revealed that high expression of HHLA2 has important values in predicting the response to ICB and indicating improved PFS and OS in patients with advanced and unresectable melanoma, suggesting that HHLA2 may serve as a costimulatory ligand in melanoma, which renders it as an ideal biomarker for immunotherapy.